2018
DOI: 10.3390/rel9010032
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatry, a Secular Discipline in a Postsecular World? A Review

Abstract: Postsecular theory is developing in academic circles, including the psychiatric field. By asking what the postsecular perspective might imply for the secular discipline of psychiatry, the aim of this study was to examine the postsecular perspective in relation to the secular nature of psychiatry, by way of a narrative review. In a systematic search for literature, relevant articles were identified and analyzed thematically. Thirteen articles were included, and three intertextual themes were identified, which r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…This brings an aspect to the international debate within psychiatry on the “neutral” psychiatrist, that is, that the psychiatrist can approach the patient from a neutral or value free position, and considering whether identifying psychiatry as a secular discipline is not a biased position in itself (Cook, Powell, Sims, & Eagger, 2011). It is now generally acknowledged that a “neutral” position is untenable in the recognition that the individual is always speaking from some position and that this cannot be a neutral position (Greenberg 2001; Nissen, Gildberg, & Hvidt, 2018). Likewise, recent research is asking whether (value) neutrality is even desirable (Kørup et al, 2018).…”
Section: Analyzing Datamentioning
confidence: 99%
“…This brings an aspect to the international debate within psychiatry on the “neutral” psychiatrist, that is, that the psychiatrist can approach the patient from a neutral or value free position, and considering whether identifying psychiatry as a secular discipline is not a biased position in itself (Cook, Powell, Sims, & Eagger, 2011). It is now generally acknowledged that a “neutral” position is untenable in the recognition that the individual is always speaking from some position and that this cannot be a neutral position (Greenberg 2001; Nissen, Gildberg, & Hvidt, 2018). Likewise, recent research is asking whether (value) neutrality is even desirable (Kørup et al, 2018).…”
Section: Analyzing Datamentioning
confidence: 99%
“…In a culturally entwined and pluralistic world, an existential orientation, be it secular, spiritual, or religious, is a conscious choice for some and not so for others (Taylor, 2007). For some it is irrelevant, for others it is the Archimedean point around which everything else revolves (Damberg Nissen et al, 2018). However, when faced with life-threatening illness these existential questions have a strong tendency to surface (Hvidt et al, 2017(Hvidt et al, , 2019.…”
Section: The Ontological Grounding and The Meaning-making Matrixmentioning
confidence: 99%
“…With the words of Charles Taylor, it can be argued that the existential orientations in contemporary Western culture, be they secular, spiritual or religious, are cross-pressured in a figurative force-field, they are continuously contested by the presence of each other and work upon each other as interior "pressures" or "forces, " thereby fragilizing each other (Taylor, 2007). For healthcare, this may explain why it is difficult to approach existential orientations due to the presence of barrier pressures (the bias of the surrounding (cultural) context) of, for instance, ethics, professional boundaries, and scientific discourse, that are countered by facilitating pressures of, for instance, compassion and sense of a patients' spiritual needs (Damberg Nissen et al, 2018). These types of barriers and facilitators work against each other in the clinic and constitute the force field of opposing cross-pressures (barriers and facilitators) that HCPs need to engage in the encounter with each new patient.…”
Section: The Ontological Grounding and The Meaning-making Matrixmentioning
confidence: 99%
“…After all, 'existential', 'spirituality', and 'religion' are merely words constructed to capture human experience (at the macro level), not necessarily capturing this experience at the (micro) individual level or cross-culturally (Bowman and Valk 2015;Mignolo 2011). What is important is remembering that there is a difference between spiritual care as an intervention, and what is potentially the Archimedean point of the individual worldview of the patient, around which everything else revolves (Nissen et al 2018). Anthropology, sociology, and the study of religion have shown that human life and experience are not reducible to, or containable in, the concepts we try to develop to describe the human worlds, and do not lend themselves to such simple descriptions (Descola 2014;Holbraad and Pedersen 2017).…”
Section: Spiritual Care Spirituality and Religionmentioning
confidence: 99%
“…It could be argued that it would make a clearer and stronger catalogue to completely exclude any secular existential focus and exclusively center on the spiritual and religious aspects. However, this would lead to the exclusion of instruments developed in more secular grounded contexts, and thereby exclude instruments that deal with the spiritual and religious in post-secular environments where the religious/spiritual may be approached through a secular vocabulary (Nissen et al 2018). This also bears into cross-cultural discussions of what spirituality is and different understandings of the concept.…”
Section: Spiritual Care As a Processmentioning
confidence: 99%